Influence of the construction sector on the gross domestic product of the oil and gas industry (Economics and region, 2022)
The article describes the role of construction development in the oil and gas industry in turning the country into an attractive investment resource center. Here, on the basis of statistical data, the dynamics of the development of investments aimed at construction and installation works, income from the oil and gas sector and GDP in the Republic of Azerbaijan are analyzed and evaluated. In the research work, a correlation-regression analysis of the dependence between investments aimed at construction and installation works in the Republic of Azerbaijan, income from the oil and gas sector and GDP was carried out on the basis of the Eviews-12 software package. On the basis of the research work, it was established that the increase in investments aimed at construction and assembly works in the Republic of Azerbaijan and the increase in income from the oil and gas sector significantly cause the increase in GDP in the Republic of Azerbaijan.
Keywords: oil; gas; construction and assembly work; model; correlation; regression; program complex; adequacy